The correlates of teacher turnover: An updated and expanded Meta-analysis of the literature. (November 2020) - Nguyen, Tuan D.; Pham, Lam D.; Crouch, Michael; Springer, Matthew G.
Abstract: Rigorous research examining the correlates of teacher turnover has grown in recent years. However, the most recent meta-analytic synthesis of this literature was published over a decade ago. To update our collective understanding and highlight advances in this literature, this meta-analysis reviews findings from 120 studies of factors associated with teacher turnover. In addition to providing a novel synthesis using the most up-to-date meta-analytic methods and better quality data than ever before, we contribute evidence to support an expanded conceptual framework for understanding teacher turnover. This framework adds several underexamined factors influencing teacher turnover, provides more nuance to factors previously studied, highlights the growing influence of educational policies external to the school, and accounts for an emerging awareness of the interplay between teacher and school characteristics. This paper reports both results for how various teacher, school, and workforce factors are associated with teacher turnover and discusses the policy implications using our expanded theoretical framework. Highlights: This study is a comprehensive study of the factors of teacher attrition and retention. We synthesize findings from 120 studies for three primary categories and nine subcategories. Findings for each factor are discussed and contrasted with prior reviews. Gaps in the empirical literature are highlighted and policy implications are discussed.